Factors Related to Body Image of Adolescents with Thalassemia - Punriddum, Jirakan; Sanasuttipun, Wanida; Sangperm, Parnnarat (Nursing Science Journal of Thailand, 2018)
Purpose: This study aimed to examine the relationships between related factors: age, gender, perceived reactions from others, social support, and body image of adolescents with thalassemia. Design: Correlational study. Methods: The study sample included 126 patients, aged between 13-18 years, who attended Pediatric Hematology Clinics in three tertiary care public hospitals. The subjects were recruited by convenience sampling. Data were collected using questionnaires: a demographic data form, perceived reactions from others questionnaire, social support questionnaire, and body image of adolescents with thalassemia questionnaire. Data were analyzed using descriptive statistics, Pearson’s correlation coefficient and Chi-square. Main findings: The study results indicated that adolescents with thalassemia perceived their body image at a poor level. Patient’s age was negatively correlated with body image (r = - .18, p < .05). Two factors were positively correlated with body image; that is, perceived reactions from others (r = .45, p < .01) and social support (r = .20, p < .05). However, gender was not correlated with body image in adolescents with thalassemia (χ2 = .74, p = .39). Conclusion and recommendations: Adolescents with thalassemia had poor body image and the correlated factors included age, perceived reaction from others, and social support. Healthcare providers, especially professional nurses, should promote caregivers, family members and other related persons to have good understanding towards these adolescents and express positive reaction as well as provide sufficient social support to them in all aspects. These would assist adolescents with thalassemia to perceive better body image.